Utilization of HCR-22 as Substitute for R-22 in Fish Refrigeration Unit - I Made Aditya Nugraha; Marcus Samusamu (Jurnal Airaha, 2022)
Since each refrigerant has different vaporization and condensation temperature and pressure, the capacity and working conditions of each system depend on the type of refrigerant used. The criteria for a suitable refrigerant for a refrigeration system are determined by its thermodynamic, chemical, and other factors. This research aims to analyze the capacity and scope of work of refrigerator components that use R-22 refrigerant to be replaced with HCR-22 in a 1.7 TR refrigeration fish refrigerator without having to replace components. This research was carried out from December to March, on a regular fishing vessel, Alalunga Vessel. The research was conducted by reviewing and analyzing the application of refrigerant HCR-22 and R-22 in the refrigerator unit. The results of the analysis of the capacity and scope of work of the components show that HCR-22 refrigerant has a higher advantage than R-22. These high advantages have a positive reaction to the refrigeration effect and refrigerant workload, which include an increase in heat absorption capability, a decrease in compressor and electric motor energy, a decrease in the compression ratio, an increase in the compressor coefficient achievement.